Vaccine Evolution and Its Application to Fight Modern Threats - Andreano, Emanuele; D'Oro, Ugo; Rappuoli, Rino; Finco, Oretta (Frontiers in Immunology, 2019)
Before the development of the first vaccine, infectious diseases were a major cause of death around the globe with life expectancy estimated to be <50 years. Three measures have helped to drastically reduce the burden of infectious diseases but only vaccines have proven to be able to eradicate infectious agents. Herein, we describe new methodologies that have paved the way for what is currently known as modern vaccinology and the use of vaccines to tackle antimicrobial resistance, the biggest global threat of our time.